Cytoplasmic Staining of TTF-1 Antibody in the Diagnosis of Hepatocellular Carcinoma: Study on 299 Cases Using Tissue Microarray. (6th July 2011) - Cao, Qinghua; Liu, Fang; Xiao, Ping; Wang, Min; Lin, Yuan; Ye, Ziyin; Che, Lihong; Xue, Ling
Abstract : The diagnosis of hepatocellular carcinoma (HCC) remains obscure in some complicated cases. Thyroid transcription factor-1 (TTF-1) was presumed to be helpful in the diagnosis of HCC. This paper aims to study the utility of TTF-1 in the diagnosis and differential diagnosis of HCC and to assign clinicopathological correlations. Immunohistochemical detection of TTF-1 is performed with tissue microarray which contains a total of 781 cases including 299 hepatocellular carcinomas (HCCs), 31 intrahepaticcholangiocarcinomas (ICCs), 86 metastatic adenocarcinomas (MACs), 5 metastatic hepatocellular carcinomas (mHCCs), 9 hepatoblastomas (HBs), 40 renal clear cell carcinomas (RCCs), 215 adjacent nonneoplastic hepatic tissue, and 96 normal hepatic tissue. The result shows that TTF-1 is positive in 55.2% (165/299) HCCs, 6.4% (2/31) ICCs, 3.5% (3/86) MACs, 60% (3/5) mHCCs, 33.3% (3/9) HBs, 0% (0/40) RCCs, 99.0% (213/215) adjacent nonneoplastic hepatic tissue, and 95.8% (93/96) normal hepatic tissue. Expression of TTF-1 is correlated with differentiation of HCC, but not with patients' age, gender, serum AFP, tumor size, number of tumor nodules, and tumor thrombus in vein or bile duct. These data suggest that TTF-1 antibody is sensitive and specific in HCC and might serve as a candidate for the diagnosis and differential diagnosis of HCC.